Sign and logical subject in Hegel - Sánchez de León Serrano, José María (Estudios de Filosofía, 2008)
The paper examines the essential connection between the Hegelian concept of sign and the functioning of speculative discourse in the Science of Logic. Starting from the unresolved tension in Kantian philosophy between the significant capacity of discourse and its auto-referentiality, there will be a focus on the Hegelian intent to resolve this tension in his treatment of language, which is to be found in the Encyclopedia of Philosophical Sciences. We will thus uncover the subtle way in which the Hegelian conception of sign enables the overcoming of the restrictions that Kant imposes on philosophical discourse without defying the basic prescription of Critical Philosophy, according to which all thinking has to be associated with an intuition in order to constitute a knowledge which pretends to be valid. Based on that result and concentrating on the very structure of the sign as Hegel conceptualizes it, we will then try to shed some light on the exact functioning of logical discourse and its basic moments – understanding, dialectics and speculation – by means of the specific example of the first three determinations of Logic: Being, Nothing and Becoming.